AKOMODASI KOMUNIKASI DALAM INTERAKSI ANTARBUDAYA MASYARAKAT SUKU MELAYU DAN SUKU NIAS DI DESA PANTAI RAJA KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR - Sari, Novita; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Indonesian slogan namely Bhineka Tunggal Ika (Different But Still One). Humans are required to be able to interact with other humans, even though among them have cultural differences. Like the Malay tribe and the Nias tribe in Pantai Raja Village, Perhentian Raja District, Kampar Regency. At first the Nias tribe had difficulty in using Indonesian and living in groups so that it was difficult to interact with the Malay tribe, now the Nias tribe was able to accommodate the culture of the interlocutors. Each communication accommodation process has three strategies used, namely the strategy of convergence, divergence and excessive accommodation. This study aims to determine the strategy of excessive convergence, divergence and accommodation carried out by the Malay tribe and Nias tribe in Pantai Raja Village, Perhentian Raja District, Kampar Regency. This study uses a qualitative method. Research location in Pantai Raja Village, Perhentian Raja District, Kampar Regency. The subjects of this study were Malay tribes and Nias tribes with 10 people selected purposively. Data collection techniques are carried out through observation, interviews and documentation. The data analysis technique of this study uses the Huberman and Miles Interactive analysis model. The results of this study indicate that the convergence strategy carried out by ethnic Malay and Nias tribes in Pantai Raja Village is to adopt the language of the interlocutor, make body movements that indicate attraction, adjust speech and not limit the distance of the interlocutor, use jewelry and clothing that do not reflect differences with his interlocutor. The divergence strategy that is carried out is that there is no attempt to use the language of the interlocutor, do not make gestures that show interest when communicating, use their own culture of speech, limit distance and ignore the distance needs of their interlocutors, use jewelry and perfumes to highlight differences to the interlocutor. The cause of excessive accommodation labeling is too much in telling the experience and knowledge of the speaker and errors in the use of the language of the interlocutor. Keyword : Intercultural Communication, Accommodation Communication, Convergence, Divergence, Overaccomodation